Effects of photoperiod and night‐time aeration rate on swim bladder inflation and survival in Pacific bluefin tuna, Thunnus orientalis (Temminck & Schlegel), larvae. (22nd February 2017) - Kurata, Michio; Tamura, Yoshiki; Honryo, Tomoki; Ishibashi, Yasunori; Sawada, Yoshifumi
Abstract: Success of swim bladder inflation (SBI) is crucial for early survival of Pacific bluefin tuna (PBF) larvae, because it reduces larval sinking death by enhancing buoyancy. In Experiment 1, we examined the effect of photoperiod on SBI and survival in PBF larvae by comparing photoperiods of 9L: 15D (9L), 14L: 10D (14L: natural photoperiod), 19L: 5D (19L) and 24L: 0D (24L) during 2–10 days post hatch (dph). In Experiment 2, the combined effects of photoperiod (24L and 14L) and nighttime aeration rate (enhanced night‐time aeration: ENA of 1300 mL min −1 as a countermeasure for sinking death and 130 mL min −1 ) on the survival and SBI were also examined during 2–10 dph. Moreover, in Experiment 3 the effect of photoperiod on vertical distribution of larvae in night‐time was examined on 3–5 dph. Photoperiod of 24L in Experiment 1 significantly inhibited SBI compared with 14L and 19L; nevertheless, it significantly improved survival compared with other photoperiods with a dark period. On the other hand, the shortened light period (9L) showed significantly reduced SBI and also survival. In Experiment 2, the countermeasure for sinking death of ENA under 24L did not further improve the survival; rather it tended to reduce the survival. In Experiment 3, larvae distributed less in the bottom layer in 24L than in 14L, suggesting the reducing effect of 24L on sinking death. The results indicate that 24L without ENA is suitable for survival which is the most serious problem in PBF larviculture.